A Report of a Solid Source Dempster Type Double Focusing Mass Spectrometer - Horsley, Robert (My University, 1950)
A description of a Dempster type double focusing mass spectrograph, converted to a mass spectrometer is reported. The latter part of the thesis deals with an investigation of a Shaw type solid ion source. Ten microgram samples of VaCl2 and SrCl2 yielded measurable ion currents of 1.0 x 10-11 amperes. Results with UF4 and PbI2 are also reported.
Keywords: Dempster; double focusing mass spectrometer; mass spectrometer; solid source dempster